Letter from the President (Journal of EAHIL, 2015)
Dear Colleagues, with 2015 we begin a new two-year cycle in the life of our Association, and I would like to use this letter toÂ thank those who have just finished their terms of office, and welcome those who are new or continuing inÂ roles for this next period...Â